Ochrona środowiska - Lisowska, Alicja (OTO Agencja Reklamowa, 2014)
International cooperation on environmental protection nowadays takes various forms and is undertaken by various subjects. Practice shows that it is international organisations, which function both globally and locally, that are among the leading subjects actively engaged in undertakings that serve the natural environment and its preservation. Having regard to the criterion of activity, it can be observed that these organisations differ widely in respect of the strength and degree of their commitment to pro-environmental activities. This article focuses only on those organisations whose activity and adopted solutions serve the natural environment and substantially contribute to its preservation.
Keywords: organizacje międzynarodowe; politologia; prawa człowieka; demokracja; pomoc humanitarna; migracje; patologie; bezpieczeństwo; terroryzm międzynarodowy; ochrona środowiska